UNAPPRECIATED DIMENSION OF CARL SCHMITT’S THOUGHT - Jokubaitis, Linas (Politologija, 2015)
The main concern of this paper is the analysis of political romanticism and political theology. Today „Politische Romantik“ is regarded as a work in the field of aesthetics or XIX century intellectual history. Contemporary interpretations of Schmitt’s work downplay the importance of this early treatise. The analysis presented in this paper aims to throw a new light on current discussions about German thinker. The major task of this work is to demonstrate that we cannot understand the entirety of his thought without understanding theoretical arguments presented in „Politische Romantik“. This book has to be understood as more than just a historical study, it offers a fundamental political critique. Schmitt understood political romanticism as a form of occasionalism that subjectifies the main factor of traditional occasionalist systems: God. He saw in romanticism the disintegration of traditional metaphysical and theological concepts. In his oppinion, romantic subject treats the world as an occasion for his artistic productivity and is not capable of political and moral decisions. This means that romanticism becomes a metaphysical and political problem. In this paper I want to present an interpretation, according to which, Schmitt developed his understanding of political theology as a concrete opposition against political romanticism. Today scholars agree that political theology should be understood as the core of his entire work. One can understand the essence of political theology better by looking at it as a polemic against political romanticism. The analysis presented in this paper tries to show that one has to understand Schmitt’s work as based on fundamental tension between what can be described as political romanticism and political theology. Contemporary political thinkers have found the work of Schmitt very stimulating. This paper aims to show that by understanding political romanticism as one of his fundamental polemical opponents we can gain a better understanding of Schmitt and contemporary political reality.